Highly active antiretroviral therapy and tuberculosis control in Africa: synergies and potential - Harries Anthony D.; Hargreaves Nicola J.; Chimzizi Rehab; Salaniponi Felix M. (The World Health Organization, 2002)
HIV/AIDS (human immunodeficiency virus/acquired immunodeficiency syndrome) and TB (tuberculosis) are two of the world's major pandemics, the brunt of which falls on sub-Saharan Africa. Efforts aimed at controlling HIV/AIDS have largely focused on prevention, little attention having been paid to care. Work on TB control has concentrated on case detection and treatment. HIV infection has complicated the control of tuberculosis. There is unlikely to be a decline in the number of cases of TB unless additional strategies are developed to control both this disease and HIV simultaneously. Such strategies would include active case-finding in situations where TB transmission is high, the provision of a package of care for HIV-related illness, and the application of highly active antiretroviral therapy. The latter is likely to have the greatest impact, but for this therapy to become more accessible in Africa the drugs would have to be made available through international support and a programme structure would have to be developed for its administration. It could be delivered by means of a structure based on the five-point strategy called DOTS, which has been adopted for TB control. However, it may be unrealistic to give TB control programmes the responsibility for running such a programme. A better approach might be to deliver highly active antiretroviral therapy within a comprehensive HIV/AIDS management strategy complementing the preventive work already being undertaken by AIDS control programmes. TB programmes could contribute towards the development and implementation of this strategy.